Molecular analysis of antagonist fungi isolated from plantations of cocoa (Theobroma cacao) from north of Santander (2021)
Molecular biology techniques have been used in order to obtain specific species genetic markers, find polymorphic differences and provide the necessary information for the identification of nucleotide sequences related to pathogenicity factors in species related to biological control. At present, biological control is considered indispensable in the strategies of sustainable agriculture with agroecological base in crops, growing interest in Colombia such as cocoa (Theobroma cacao L.). Molecularly analyze different strains of antagonistic fungi with biotechnological potential in order to elucidate genomic similarities and the search for DNA fragments related to pathogenicity factors. The technique of RAPD (Randomized Amplified Polymorphic DNA) was standardized, using 10 primers, and the pr1 gene was amplified using the PCR technique using 6 pairs of primers. An initial classification of the population of antagonistic fungi was achieved and the diversity of the isolates was also demonstrated. In addition, three genes of the Beauveria bassiana, Trichoderma yunnanense and Purpureocillium lilacinus strains were amplified, which were found to encode a family of proteases designed to exert antagonistic activity against a wide range of hosts. It can be inferred that the strains under study are good initial candidates for the formulation of biopreparations destined to the biological control of plague organisms in crops of agricultural interest in the region, due to the fact that traits and genes were found that will allow to exert a wide antagonistic action.